Glocal Zen in Italy: A Preliminary Exploration of the Underlying Dynamics - Dessì, Ugo (Religions, 2022)
This article focuses on three Zen meditation groups operating in Italy from the perspective of glocalization. Based on ethnographic fieldwork and practitioners’ narratives, it explores the dynamics underlying the making of glocal Zen with reference to the internal structure of individual religious worlds and its reshaping through the creative incorporation of zazen or zazen-like meditation. My analysis also indicates that there are at least three main factors constraining these processes of glocalization: Availability, or the way in which Zen meditational techniques become accessible (or not) to individual practitioners through global religious exchanges; global consciousness, which relates to the way in which changes in collective consciousness encourage individuals to see themselves as global actors and their Zen practice as globally relevant; and resonance, which speaks of the way in which Zen meditation is selected by individual practitioners for their glocal practices based both on its perceived congruence with their preexisting religious worlds and its usefulness for the solution of specific problems.